Enhancing university remote language learning through innovative applications of artificial intelligence technologies amidst global challenges - N. Sarnovska; J. Rybinska; Yu. Mykhailichenko (Викладання мов у вищих навчальних закладах освіти на сучасному етапі: Міжпредметні зв'язки)
In recent years, the integration of artificial intelligence (AI) technologies has revolutionised various industries, and education is no exception. One area where AI is making significant strides is in distance learning of foreign languages at the university level. The purpose of the article is to examine the many ways in which AI technologies can be used to improve the efficiency and effectiveness of foreign language learning in virtual classrooms based on a personalised approach to learning and to outline an algorithm for utilizing artificial intelligence in foreign language learning, which aims to provide a structured approach for integrating AI tools and technologies into language learning processes. The scientific novelty of the study lies in its comprehensive exploration and integration of cutting-edge AI technologies within the context of university remote learning for foreign languages. The emphasis on personalized learning paths and adaptive learning approaches is a novel aspect. The study delves into how AI algorithms analyse individual learner data to tailor educational content, providing a customized and adaptive learning experience. This focus on individualized instruction represents a departure from traditional one-size-fits-all language education methods. Research Methods. To conduct a comprehensive study on the use of artificial intelligence technologies in university remote learning of foreign languages, a mixed-methods research approach is employed. This involves both quantitative and qualitative research methods to gather a holistic understanding of the impact and effectiveness of AI technologies in language education. Conclusions. Integrating AI technologies into university remote learning for foreign languages represents a transformative shift in how languages are taught and acquired. By personalizing learning paths, providing intelligent tutoring, incorporating conversational practice, utilizing gamification, automating assessment, and leveraging virtual reality, AI is reshaping language education to be more engaging, effective, and tailored to individual student needs. As these technologies continue to evolve, the future of language learning promises to be dynamic, interactive, and increasingly accessible to learners worldwide.